2018
DOI: 10.3389/fnana.2017.00138
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Plastic Processes in Migraine with Aura: A Diffusion Weighted MRI Study

Abstract: Background: Formerly white matter abnormalities in a mixed group of migraine patients with and without aura were shown. Here, we aimed to explore white matter alterations in a homogeneous group of migraineurs with aura and to delineate possible relationships between white matter changes and clinical variables.Methods: Eighteen patients with aura, 25 migraine patients without aura and 28 controls were scanned on a 1.5T MRI scanner. Diffusivity parameters of the white matter were estimated and compared between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 75 publications
8
62
1
Order By: Relevance
“…In line with our CM correlation results, Szabó et al, 2017 [10], obtained a trend showing increased FA in migraine with aura patients with respect to healthy controls. In this study, based on increased FA values, the authors hypothesised that repeated painful conditions or increased cortical excitability might cause maladaptive plastic changes in migraine with aura.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In line with our CM correlation results, Szabó et al, 2017 [10], obtained a trend showing increased FA in migraine with aura patients with respect to healthy controls. In this study, based on increased FA values, the authors hypothesised that repeated painful conditions or increased cortical excitability might cause maladaptive plastic changes in migraine with aura.…”
Section: Discussionsupporting
confidence: 91%
“…Previous whole-brain TBSS studies found white matter differences between migraine patients and healthy controls [6][7][8][9][10][11]52]. Most of these studies report decreased FA in migraine patients with respect to healthy controls, but one study showed increased FA in migraineurs with respect to healthy controls; in this study, Messina et al analysed paediatric patients [9], which could explain the difference.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Up to now, white matter microstructural integrity showed no differences between the two sub-groups, or the studies did not separate the subgroups for investigation (Chong and Schwedt, 2015;Szabo et al, 2012). However, there are findings showing dissimilarities in the diffusion parameters between MWA and MWoA in the visual pathway (Granziera et al, 2006;Nikoletta Szabó, 2018). Furthermore, in our recent work, we found extensive disintegration of the white matter in migraine patients with aura, but not in patients without aura (Nikoletta Szabó, 2018).…”
Section: Imaging Markers Of Migrainementioning
confidence: 83%